Senam Indonesia Bergerak Untuk Sehat - Youngky RM (Virgo Ramayana Music & Entertainment, 2010)
Isi : 1. Indonesia Bergerak / Youngky RM, 2.Indonesia Harmoni / Youngky RM, 3. Indonesia Tersenyum / Nurwan Sugess, 4. Sory Boy / Youngky RM, 5. Sahara / Emen, 6. Kucari-Cari/ / Youngky RM, 7.Gantengnya Pacarku / Yalis Adi Luhung, 8. Bunga / Thomas Arya, 9. Yamko Rambe Yamko / NN, 10. Ingat Kamu / Ririn.s